PENGARUH METODE PEMBELAJARAN DAN KEMAMPUAN AWAL TERHADAP HASIL BELAJAR MATEMATIKA (Studi Eksperimen di MAN 3 Jakarta ) - Farida Hanun (Pusbindiklat - LIPI, 2010)
The aim of this research is to try the effect of teaching method in increasing study result of student in mathematicinterconnected with first ability of student. The research was conducted at MAN 3 east Jakarta at the firstsemester of the academic year 2008-2009 . The sample was selected by simple random sampling technique andthe size was 84. This research used experiment method with factorial design 2 x 2 and the data were analyzed byusing Two-way Anova and T- test at the level of significance α = 0,05. The resulted in four findings i.e.: 1) Resultof study on the students who used inquiry methods was higher than those used conventional method, 2) Therewas interaction influence between teaching methods and first ability about the result study of mathematics, 3) Theresult study of mathematics students that have high first ability who used inquiry method was higher than thoseusing conventional methods, 4) The result study of mathematics students that have low first ability who used inquirymethods was lower than used conventional methods